The analysis of Bokoharjo digital marketing communication media in promoting its potential - Eko Prasetyo Nugroho Saputro; Pratiwi Wahyu Widiarti; Ulfah Hidayati; Fikri Disyacitta (Universitas Negeri Yogyakarta, 2023)
Bokoharjo village is located at a strategic tourist destination including Boko Temple, Banyunibo Temple, Barong Temple, Ijo Temple, Breksi Hills, and Obelix Hills which requires to be developed. The development of Bokoharjo Village as a tourist village can be realized through digital marketing communication to introduce its potential products and attractions to the wider community so that the economic sector in Bokoharjo Village can grow. This research aims to: (1) identify the existing digital marketing communication media in Bokoharjo Village (2) analyze the need for digital marketing communication media in Bokoharjo Village, and (3) identify the potential and attractions of Bokoharjo village to be promoted. This research was conducted at Bokoharjo employing descriptive-qualitative methods. This initial research provided useful insight for the development of digital marketing communication media which comform to the needs and potential of Bokoharjo Village to advance Bokoharjo as a tourism village. The research results show that the digital marketing communication media in Bokoharjo include website, Instagram, Facebook, Twitter, WhatsApp which are not well managed. The media needed by Bokoharjo is an integrated media platform which contains the typical potential of Bokoharjo. The Bokoharjo potentials that can be promoted consist of Banyunibo Temple, Banyunibo Cliff, and Shibori Batik, Agricultural Commodity, and Orchid.Keywords: Media, Communication, Marketing, Digital, Bokoharjo.